(untitled) (GESTIÓN Y TENDENCIAS, 2019)
This column argues for the need to broaden the discussion of labor relations in Chile. It contends that, by dint of focusing the debate on the problem of labor legislation, we have lost sight of elements that are fundamental to understanding the relationship between unions and companies in the country. The author describes some of these elements and proposes lines of research relevant to improving our understanding of the dominant labor model.